Effect of the Method of Application of Supplementary Phosphorus on the Yield and Nutritive Value of Alfalfa - SOROUR, F. A.; SALMAN, A. J.; EL-FALEIT, J. H. (The Libyan Journal of Agriculture, 2023)
Supplementary phosphorus application in the sandy soil of the Faculty of Agriculture Farm, Sidi El Misri, Tripoli, Libya, resulted in a significant increase in the fresh and dry yields of alfalfa. However, the percentage dry matter was not significantly affected by the phosphorus application. Alfalfa responded better to foliar spray treatment of phosphorus than to soil application treatment. This may be due to the limited root growth and/or phosphorus fixation in the soil. Phosphorus application resulted in an increase in crude protein, crude fat, crude fiber, mineral matter, and nitrogen-free extract. Such increase was only significant in the case of crude fat. Percent digestible protein, percent digestible nutrients and nutritive ratio of alfalfa . were not significantly different among the different treatments.